Activities of the Lithuanian Mathematical Society in 2018–2021 - Leipus, Remigijus (Lietuvos matematikos rinkinys, 2021)
The article gives a survey of mathematical life and activities of the Lithuanian Mathematical Society during the past four years.
Keywords: mathematical activities in Lithuania